A DESCRIPTION OF DEFENSE ECONOMY AS A SCIENCE: THE DEVELOPMENT OF A COLD WAR TIME TO A CONTEMPORARY STUDY - Endro Tri Susdarwono (Jurnal Utilitas, 2020)
The approach in this study uses a descriptive approach, the approach is intended to describe the description of the defense economy as a science by emphasizing the study of defense economics, especially the issues of study that developed during the cold war and post-cold war studies and the development of defense economy studies according to contemporary definitions. Defense economics is a study of defense costs that examines issues of defense and peace using economic analysis and methods which include microeconomic and macroeconomic studies such as static and dynamic optimization, growth theories, distribution, comparison of statistical and econometric data (use of statistical economic models). The post-Cold War Defense Economy is no longer just about managing logistical resources during wartime, managing the supply of weapons on the battlefield or war winning strategies by controlling economic resources. Understanding of the Defense Economy today has shifted to issues such as conflict, terrorism, peace, disasters to social problems ranging from food to health.